WIRID PENGAJIAN DAN KOLEKTIVITAS MASYARAKAT DI DUSUN INDAH DESA PINANG SEBATANG TIMUR KECAMATAN TUALANG KABUPATEN SIAK - Asmawati "; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Wirid recitation is an activity smelling of Islam that is done both men and women to learn the practice of the Qur'an, dhikr, prayer and hadith.Wirid study is not only to get closer to the creator but also to get closer to usto our environment that is man with the creator, man with man and man with his environmen. With the wirid of this study of course the security that always happens so as to create a relationship of solidarity cohesiveness, and familiarity whether it is true with the wirid this study can strengthen friendship between fellow people in pinang village sebatang if it is true whether they are as familiar as it is only because of formalities in an organization only. The Problem Formulation is how wirid teaching activities and what does wirid teaching activity have to do with the social activities of the community there. The subjects of this study amounted to 9 mosque chairmen, wirid chairmen of teaching and members of the teaching wirid, in determining the subject the author studied using purposvie sampling techniques. Data collection is conducted using in-depth interview, observation, and documentation methods. The results showed that it is true that the existence of such study wirid can create friendship and harmony between peoples there even though they have different cultural and ethnic backgrounds if there are conflicts that can be resolved faster with the wirid of teaching so that conflicts social inequality are minimal to occur. But they cannot be said to be familier because they are bound by the rules in which the study wirid must be adhered to in accordance with the mutual agreement. Their togetherness is only a formality, so it can be concluded that they can be said to be close but can not be said to be famillier.   Key words: wirid studying and community collectivity